Implementation of the Science Mobile Learning Application for Solar System Material for Class VI Emereuw Jayapura Elementary School - Sampebua, Mingsep Rante; Sampe, Aris; Wororomi, Jonathan K. (Abdi Masyarakat, 2025)
The urgency of PNBP community service in 2024 is that teachers need to implement mobile learning applications as interactive multimedia learning media for science on solar system material for grade VI elementary school students. This is necessary because students find it difficult to understand the solar system subject matter and do not know what planets are in the solar system using textbook teaching materials and students get bored quickly and are less interested because students only imagine the solar system based on the teacher's explanation on the board. The purpose of this community service is the transfer of science and technology to implement mobile learning applications as interactive multimedia learning media for science on solar system subject matter for grade VI elementary school students. Community service activities are carried out using lecture methods, discussions, questions and answers, demonstrations and practices for using mobile learning applications for science, as well as evaluation of community service activities. The targeted output is that elementary school students can use interactive learning media for mobile learning applications for science to improve the quality of learning solar system material and the results of community service activities in the form of articles published in community service journals.